2015
DOI: 10.2215/cjn.04260415
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Renal Insufficiency Cohort Study (CRIC)

Abstract: The Chronic Renal Insufficiency Cohort (CRIC) Study is a United States multicenter, prospective study of racially and ethnically diverse patients with CKD. Although the original aims of the study were to identify novel predictors of CKD progression and to elucidate the risk and manifestations of cardiovascular disease among nearly 4000 individuals with CKD, the CRIC Study has evolved into a national resource for investigation of a broad spectrum of CKD-related topics. The study has produced >90 published scien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
74
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 102 publications
(82 citation statements)
references
References 51 publications
1
74
0
Order By: Relevance
“…Depending on the age, the eGFR limits for inclusion are between 20 and 70 ml/min/1.73m 2 and the renal endpoints considered are the need for renal replacement therapy, a reduction of eGFR by 50% and/or a decline of eGFR by at least 25 ml/min/1.73m 2 [7, 8]. When compared to non-diabetic participants, patients with diabetes were more likely to suffer from comorbidities like myocardial infarction (28 vs 16%), congestive heart failure (14 vs 6%) or peripheral vascular disease (10 vs 3%) [9]. The mean eGFR in diabetic participants was 41 ml/min/1.73m 2 , the mean HbA1c level 7.7% and about 80% were on RAS blocking agents [9].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the age, the eGFR limits for inclusion are between 20 and 70 ml/min/1.73m 2 and the renal endpoints considered are the need for renal replacement therapy, a reduction of eGFR by 50% and/or a decline of eGFR by at least 25 ml/min/1.73m 2 [7, 8]. When compared to non-diabetic participants, patients with diabetes were more likely to suffer from comorbidities like myocardial infarction (28 vs 16%), congestive heart failure (14 vs 6%) or peripheral vascular disease (10 vs 3%) [9]. The mean eGFR in diabetic participants was 41 ml/min/1.73m 2 , the mean HbA1c level 7.7% and about 80% were on RAS blocking agents [9].…”
Section: Discussionmentioning
confidence: 99%
“…When compared to non-diabetic participants, patients with diabetes were more likely to suffer from comorbidities like myocardial infarction (28 vs 16%), congestive heart failure (14 vs 6%) or peripheral vascular disease (10 vs 3%) [9]. The mean eGFR in diabetic participants was 41 ml/min/1.73m 2 , the mean HbA1c level 7.7% and about 80% were on RAS blocking agents [9]. …”
Section: Discussionmentioning
confidence: 99%
“…Regarding depression, it has been repeatedly shown that depression is common and underrecognized in patients with advanced CKD or end-stage-renal disease [43] . Whether or not less severe forms of impaired kidney function (eGFR ≥ 30 or even ≥ 45 mL/min/1.73 m 2 ) are associated with more depressive symptoms compared to preserved kidney function (eGFR ≥ 60 mL/min/1.73 m 2 ) is still unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Kidney function was measured as eGFR using the CKD-EPI (CKD Epidemiology Collaboration) creatinine equation; and albuminuria quantified as total albumin excretion in a 24 hour urine collection. Per the CRIC protocol, measured iothalamate glomerular filtration rate (iGFR) was performed by urine clearance in 1/3 of the cohort 16,22 .…”
Section: Methodsmentioning
confidence: 99%